Pengaruh Kepemimpinan Transformasional, Budaya Organisasi dan Kompetensi Terhadap Kinerja Karyawan pada PT. Bhineka Mitra Sejati Kota Semarang - Ahmad Setyawan; Lie Liana (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze how big the influence of transformational leadership, organizational culture, competence is on the performance of PT employees. Bhineka Mitra Sejati Semarang City. This research involved 93 employees from PT Bhineka Mitra Sejati as the population. The sampling method used was purposive sampling with the criteria that the respondent had worked for at least 1 year at PT Bhineka Mitra Sejati. The number of samples taken in this research was 82 respondents, in accordance with the application of Roscoe's theory. Data analysis in this study used respondent description tests, variable descriptions, validity tests, reliability tests, F tests, coefficient of determination (R²) tests and hypothesis test results. The results of this research show that transformational leadership has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, and competence has a positive and significant effect on employee performance. The conclusion is that there is an influence of transformational leadership, organizational culture, and competency on employee performance. Keywords: Competence, Employee Performance, Transformational Leadership, Organizational Culture,